Conflict of Interest Between The Family and The State In Sophocles' Antigone (1912) : Psychoanalytic Criticism - SOLIAH, NUNUNG (2011)
This study aims to explore the conflicts of interest between the family and the state in Sophocles's Antigone. The objective of the research is to analyze the drama based on its structural elements and to analyze the poetry based in psycho analytic criticism. The researcher employs a qualitative method. In this method, the researcher uses two data sources, namely primary and secondary data sources. The primary data source is the drama script. The secondary data sources are reference and material related to the study. The method of data collection is library research and the technique of data collection is descriptive technique. The study shows the following conclusions. Fir st, based on the structural analysis, it is clear that in this drama, Sophocles wants to deliver a message that sometimes a conflict is hard to solve. Second, based on the psychoanalytic analysis, it is evident that Sophocles reflects a psychological phenomenon, namely the conflict of id, ego and superego.